2019
DOI: 10.3390/ijms20174240
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Docosahexaenoic Acid Is a Mediator of Fate-Decision of Adult Neural Stem Cells

Abstract: The mammalian brain is enriched with lipids that serve as energy catalyzers or secondary messengers of essential signaling pathways. Docosahexaenoic acid (DHA) is an omega-3 fatty acid synthesized de novo at low levels in humans, an endogenous supply from its precursors, and is mainly incorporated from nutrition, an exogeneous supply. Decreased levels of DHA have been reported in the brains of patients with neurodegenerative diseases. Preventing this decrease or supplementing the brain with DHA has been consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 167 publications
1
11
0
Order By: Relevance
“…First, we showed that the dietary imbalance in n-6/n-3 PUFA decreased the number of hippocampal neuroprogenitors. In agreement, docosahexaenoic acid (DHA), one of the derivates of n-3 PUFA, increases neuroprogenitors proliferation at low concentrations and promotes differentiation at higher ones [38]. Indeed, n-3 PUFA derivates promote neurogenesis in vitro without changing gliogenesis [39][40][41][42], which matches our observations in vivo (Figure 8).…”
Section: Discussionsupporting
confidence: 87%
“…First, we showed that the dietary imbalance in n-6/n-3 PUFA decreased the number of hippocampal neuroprogenitors. In agreement, docosahexaenoic acid (DHA), one of the derivates of n-3 PUFA, increases neuroprogenitors proliferation at low concentrations and promotes differentiation at higher ones [38]. Indeed, n-3 PUFA derivates promote neurogenesis in vitro without changing gliogenesis [39][40][41][42], which matches our observations in vivo (Figure 8).…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, in all cases in which it was assessed, the effects of HFD on stem cells appear to be reversible and could, therefore, potentially be corrected simply by changes in diet. Interestingly, while HFD seems to impair neurogenesis (Park H. R. et al, 2010;Ogrodnik et al, 2019), specific types of FAs, including omega-3 FAs appear to increase neurogenesis (Kang et al, 2014;Nascimento et al, 2016;Lo Van et al, 2019), suggesting that diet could be used to rescue neuronal loss in diseases and aging.…”
Section: Dietmentioning
confidence: 99%
“…First, we showed that the dietary imbalance in n-6/n-3 PUFA decreased the number of hippocampal neuroprogenitors. In agreement, docosahexaenoic acid (DHA), one of the derivates of n-3 PUFA, increases neuroprogenitor proliferation at low concentrations and promotes differentiation at higher ones [ 38 ]. Indeed, n-3 PUFA derivates promote neurogenesis in vitro without changing gliogenesis [ 39 , 40 , 41 , 42 ], which matches our observations in vivo ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%